Exploring crisis management measures taken by school leaders at the unpredictable crisis - case COVID-19 - Peltola, Jussi-Pekka; Lindfors, Eila; Luukka, Emilia (SPRINGER, 2025)
The COVID-19 pandemic was an unpredictable crisis for schools. Schools transitioned their teaching from classrooms to teaching online. The holistic safety of the schools' was under a serious threat. Various measures of crisis management aimed at upholding holistic school safety, which includes physical, social, psychological and pedagogical safety.This review employs both narrative review method and thematic analysis to investigate the crisis management measures that school leaders undertook during the 2020 COVID-19 pandemic in terms of holistic school safety while modifying key operations of the school. In addition, the stressors and resources of school leaders' were examined. The non-systematic, explorative search for literature conducted between autumn 2020 and spring 2021 yielded a total of 10 articles.School leaders' crisis management measures to maintain holistic school safety in 2020 comprised running the organization, supporting teachers, and supporting students. Extensive measures to limit physical contact posed a threat to psychological, social and pedagogical safety. School leaders worked in a stressful situation. Flexibility and human-centered approach were necessary to cope.In future crises, predicting consequences at every level is important when preparing plans and considering leaders' tasks as part of crisis management plans to ensure holistic school safety. In crisis situations, priority must be given to tackling the primary threat, but the overall impact of measures on school safety must be taken into account.